Effects of UV-A/B/C on flavonoids and related synthetic enzymes in Tetrastigma hemsleyanum - Li, Shan; Xia, Jingqing; Liu, Shouzan; Li, Zhe; Shen, Qiong; Yang, Feng; Liu, Xinhong; Bai, Yan (Frontiers in Plant Science, 2024)
Introduction Tetrastigma hemsleyanum is a folk and rare medicinal plant, and specifically, it is distributed in the south, China. To investigate the cumulative properties of its medicinal components, we examined the effect of UV light on flavonoid content and related enzyme activity changes in T. hemsleyanum. Methods The leaves and tubers were treated with UV-A, UV-B and UV-C for 1 h, 1L/23D h, 3 h and 3L/21D h (D represents darkness treatment). High-performance liquid chromatography (HPLC) analysis showed that the content of many flavonoids decreased significantly during UV-A treatment, increased after UV-B and UV-C irradiation and accumulated again after darkness treatment. Results In the root tubers of the UV-A group, naringin content in the 3L/21D h group (0.069 μg/g) was 16.30 times higher than that of 3 h group (0.0042 μg/g). The rutin content was elevated after UV irradiation but was not detected in the CK group. The test results of the enzyme-linked kit indicated that the activities of many enzymes were higher in the UV-A and UV-B irradiation groups than those in the CK group, but the results were reversed in the UV-C treatment. After darkness treatment, the activities of most enzymes were higher than those with UV irradiation alone; F3’5’H activity in the 3L/21D h group (97.25 U/L) was 1.24 times higher than that in the 3 h group (78.12 U/L) in the UV-A-treated group. Discussion The study results suggest that appropriate UV-B and UV-C irradiation, as well as darkness supplementation, had a promotive effect on flavonoids in the leaves and root tubers of T. hemsleyanum. Additionally, UV irradiation and darkness treatment enhanced the activity of most enzymes.